“Los estilos de crianza en el desarrollo de las habilidades sociales de los niños de 5 a 6 años” - Ortiz Quinapanta, Cristina Elizabeth (2022)
Social skills are the set of abilities that the human being has to interact and relate to other people, a deficient development can affect personal and social level. Social skills are learned during childhood and develop throughout growth, being the family one of the contexts that have more influence on the development of social skills during childhood. That is why the purpose of this research study is to diagnose the influence of parenting styles on the development of social skills, achieving a safer interaction in children from 5 to 6 years old at "San José de Guaytacama" Educational Unit. The research was developed through qualitative and quantitative research approaches, under the type of correlational research, and was also supported by field and bibliographic research, using the inductive method. The information was collected from a population of 79 participants, including authorities, teachers, and children, using techniques such as interviews, surveys, and observation. In order to record the data obtained, an open-ended questionnaire was applied to the authority and teachers of the high school level of the institution, a questionnaire of closed questions, addressed to parents, and a checklist used to evaluate the development of social skills in children. The analysis of the information collected led to the following conclusion: the parenting styles identified in the parents are authoritative and permissive, being the authoritative parenting style the one that favors the adequate development of social skills, while the permissive parenting style has a negative influence on skills such as conflict resolution, assertiveness, and self-control.